Interlimb asymmetries in youth tennis players: relationships with performance - Madruga-Parera, M.; Bishop, C.; Fort-Vanmeerhaeghe, A.; Beltran-Valls, M. R.; Skok, O. G.; Romero-Rodriguez, D. (The Journal of Strength and Conditioning Research, 2020)
Change of direction speed (CODS) has been highlighted as a critical component of tennis. Interlimb asymmetries have been commonly studied in jump tests, but less attention given to the topic during CODS. The aim of this study was to quantify interlimb asymmetries in jumping and CODS (during traditional and isoinertial tests) and establish their relationship with measures of physical performance. Twenty-two elite youth tennis players (16.3 ± 1.4 years) performed single-leg countermovement jump (SLCMJ), single-leg broad jump, and single-leg lateral jump, a double 180° turn CODS test, and shuffle lateral step and crossover step with an isoinertial resistance device. Paired-samples t-tests revealed significant differences between limbs for all tests (p < 0.05). Interlimb asymmetry scores ranged from 1.83 to 15.03%, and a 1-way repeated-measures analysis of variance showed significant differences between interlimb asymmetry scores across multiple tests (p < 0.05). Spearman's rank order r correlations showed significant negative relationships between CODS asymmetry and SLCMJ performance on both limbs (r = -0.50; p = 0.02 and r = -0.53; p = 0.01) and CODS performance on both limbs (r = 0.50; p = 0.02 and r = 0.63; p = 0.002). These results show the test-specific nature of asymmetries in youth tennis athletes, with the SLCMJ presenting the greatest magnitude of asymmetry. Furthermore, interlimb differences during CODS were associated with reduced performance during jumping and CODS tests, suggesting the monitoring of asymmetries within this population may therefore be warranted.